2010
DOI: 10.1055/s-0030-1262903
|View full text |Cite
|
Sign up to set email alerts
|

Acute Crystal-induced Arthritis Following Arthroplasty

Abstract: Septic arthritis at the site of previous arthroplasty is a serious medical problem with high morbidity and mortality. Even with careful physical examination and laboratory evaluation, the diagnosis of septic arthritis may be difficult to confirm and many patients undergo operative procedures for presumed infection. In patients with previous arthroplasty, a synovial fluid white blood cell count of >2,500-3,000/mm 3 in the presence of an elevated erythrocyte sedimentation rate and C-reactive protein has been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 16 publications
(19 reference statements)
0
13
0
1
Order By: Relevance
“…Joint movements were universally restricted on admission across the studies reviewed, and this was more pronounced amongst pseudogout patients with a mean reported range of motion of 57°, see table 3. [12] P Blyth & V S Pai [13] M J Archibeck et al [14] G Roberts [15] L Crawford et al [16] J C Rompen et al [17] J W Salin et al [18] J S Berger et al [19] S K Fokter et al [20] M T Freehill et al [21] A Zadaka et al [22] S Soloway [23] [25] G Holt et al [26] C Hirose & R Wright [27] P Sonsale et al [28] J L Carter et al [29] T Hunte et al [30] K Koyama et al [31] G Levi et al [32] K Harato& H Yoshida [33] Article Type Case Series ( …”
Section: Presenting Features and Clinical Examinationmentioning
confidence: 99%
“…Joint movements were universally restricted on admission across the studies reviewed, and this was more pronounced amongst pseudogout patients with a mean reported range of motion of 57°, see table 3. [12] P Blyth & V S Pai [13] M J Archibeck et al [14] G Roberts [15] L Crawford et al [16] J C Rompen et al [17] J W Salin et al [18] J S Berger et al [19] S K Fokter et al [20] M T Freehill et al [21] A Zadaka et al [22] S Soloway [23] [25] G Holt et al [26] C Hirose & R Wright [27] P Sonsale et al [28] J L Carter et al [29] T Hunte et al [30] K Koyama et al [31] G Levi et al [32] K Harato& H Yoshida [33] Article Type Case Series ( …”
Section: Presenting Features and Clinical Examinationmentioning
confidence: 99%
“…A body of case reports describe attacks of gouty arthritis after TKA, with some successfully managed medically and some requiring revision surgery. [7][8][9][10][11] A recent study using an institutional database including a total of 482 patients with gout undergoing total joint arthroplasty did find increased rates of wound healing problems and renal complications in the gout cohort as well as increased 90-day readmission rates in gout patients undergoing total hip arthroplasty. 12 Nevertheless, to our knowledge, there is no national database study in the English literature evaluating outcomes of patients with gout after TKA.…”
mentioning
confidence: 99%
“…False positive results in crystal-induced arthritis has been reported. 31,32 The sensitivities, specificities, negative predictive values, and positive predictive values of the tests are comparable in patients with inflammatory arthritis and noninflammatory arthritis. The optimal cut-offs for inflammatory and non-inflammatory arthritis are 3500/μL and 3400/μL for synovial fluid white cell count, and 88.5% and 85.1% for neutrophil percentage, * Presence of one or more of the following features: clinical or radiological suspicion of infection, erythrocyte sedimentation rate of >30 mm/h and C-reactive protein of >10 mg/l, presence of any disorder that can raise inflammatory markers, a history of wound infection, implant failure less than 5 years after arthroplasty …”
Section: Synovial Fluid Cell Count and Neutrophil Percentagementioning
confidence: 95%